Export performance and exchange rate volatility: Evidence from the WAMZ - Abu Bakarr Tarawalie; Momodu Sissoho; Mohamed Conte; Christian R. Ahortor (West African Monetary Institute (WAMI), 2013)
This paper examines the relationship between exchange-rate volatility and export performance in the WAMZ countries using quarterly data for the period 1990-2010. The paper utilizes the Engel-Granger Dynamic OLS (DOLS) estimation technique as well as the Generalized Auto Regressive Conditional Heteroskedasticity (GARCH) approach to model the real exchange rate volatility. In conformity with theoretical considerations, the results indicate that increases in the exchange-rate volatility exert a significant negative effect upon export in Liberia, Nigeria and Sierra Leone. While a positive relationship is established in the case of The Gambia, exchange-rate volatility impact on Ghana and Guinea is insignificant. The results also reveal a positive relationship between terms of trade and export performance for all the countries, indicating that improvement in terms of trade trigger increases in export performance in the WAMZ countries. Income from the rest of the world is found to have a positive effect on export performance in the WAMZ countries. The study also finds that real effective exchange rate has a negative impact on export performance in the case of The Gambia, Ghana and Nigeria, while a positive relationship is established in the case of Guinea and Liberia. However, while a positive relationship is revealed for Sierra Leone in the long run, its impact in the short run is negative. A key lesson arising from this study is that trade policy actions aimed at stabilizing the export market are likely to generate uncertain results, at best, if policymakers in the WAMZ countries ignore the stability as well as the level of the real exchange rate. Thus, if policymakers wish to target exports, policies which will ensure stability of the exchange rate should be of outmost importance.
Keywords: 330; Exchange rate volatility; Engel-Granger Dynamic OLS; export performance; GARCH; WAMZ